SOSIALISASI TERKAIT ADWARE UNTUK KEAMANAN BERINTERNET DI SMK PANTI KARYA - Ade Napila; Andrian Hidayat (Abdi Jurnal Publikasi, 2023)
Adware is a software application where advertising banners or advertising material or downloaded while the program is running, even when the device is displayed connected to the internet, or in some cases can occur while offline use. Advertisements are delivered via pop-up windows or bars that appear in the user interface program. Mobile adware is generally built for computers, but also mobile devices can become targets for adware exploits. Although adware can't be classified as a virus and doesn't pose the threat it does by other malicious files circulating on the internet, very adware inconveniences computer and mobile users if the device already has an infection. Panti Karya Vocational School is one of the educational institutions integrated program whose students are Gen Z who understand deeply access the internet. However, students have not been equipped with knowledge related to action precautions in avoiding malicious file infections on the internet, in particular regarding adware. In this case, we intend to do related outreach adware in Panti Karya Vocational Schools as a form of introduction and preventive action and persuasive so that Panti Karya Vocational School students can avoid infection and adware exploits that are scattered on the internet.